AN ANALYTICAL STUDY OF FEMINISM IN THE BOOK OF CHARLOTTE BRONTE "JANE EYRE" - Haider Jaber Husain (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Cantered on their perceptions, Jane Eyre is a well-known piece by Charlotte Bronte. The author creates a strong, freethinking woman who keeps track of true love and freedom in this book. At the time, Jane Eyre is unlike any other human. In challenging circumstances, she fights for her survival and protects her destiny. The picture of Jane Eyre compares strongly with man-dominated culture in the Victorian century. She's a young woman who has the strength to fight for her affection and her freedom. By examining Victorian periods and central aspects of feminism and Jane's perspectives, the paper refers to the present socio-economic, political and cultural sense, Jane being a feminist in the pursuit of freedom, equity, and true love. We should then examine what Jane did as a feminist in four ways: her promotion of justice, dignity, equity, and true love. Following feminist ideals, Jane Eyre eventually acquires dignity, liberty, wealth, and true love, through her relentless and courageous revolt and search. Finally, this paper is going to clarify the profound and enduring importance of this book.